2007
DOI: 10.1007/s10811-007-9185-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the production of a proteinaceous hemolytic exotoxin by wild-type strain of Synechocystis sp. PCC 6803 (Cyanobacteria)

Abstract: A proteinaceous hemolysin produced by a wildtype strain of Synechocystis sp. PCC 6803 was purified from cell-free culture supernatants by successive column chromatography on DEAE-Sepharose Fast Flow and Sephacryl S-300 High Resolution. The molecular mass of the hemolysin, determined by SDS-PAGE, was approximately 81 kDa. The hemolysin was heat labile and showed potent hemolytic activity against rabbit and sheep erythrocytes. The hemolysin started to be secreted during the exponential growth phase and accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Our previous work has confirmed that the hemolytic activity of concentrated cell-free cultures of WT PCC6803 correlates well to the features of hemolysin (Liu et al, 2008). To further this line of examination, the hemolysin crude extracts were analyzed in this study.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Our previous work has confirmed that the hemolytic activity of concentrated cell-free cultures of WT PCC6803 correlates well to the features of hemolysin (Liu et al, 2008). To further this line of examination, the hemolysin crude extracts were analyzed in this study.…”
Section: Discussionmentioning
confidence: 70%
“…Hemolysin is produced by many pathogenic bacteria (Parker, 2003;Tilley and Saibil, 2006) and several cyanobacteria (Hashimoto et al, 1976;Mitsui et al, 1988;Wang et al, 2007;Sakiyama et al, 2006;Liu et al, 2008). Hemolysis mechanisms are not only closely related to the virulence in pathogenic bacteria, but may also be an indicator of the toxicity for cyanobacteria invading some types of fish (Mitsui et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 mT during the early exponential phase (day 7 th ). The β values were selected considering different criteria (Hirano, Ohta, & Abe, 1998;Y. Z. Liu, Wang, Ru, & Zhao, 2008;Singh, Tiwari, Abraham, Rai, & Rai, 1994;Zhi-Yong, Si-Yuan, Lin, & Miao-Yan, 2007).…”
Section: Methodsmentioning
confidence: 99%